Effectiveness of interpretive signages in Taman Botani Negara Shah Alam - Abd Rashid, Nur Qistina (2018)
The purpose of Taman Botani Negara Shah Alam (TBNSA) developed was aimed to be a center of excellence in education, scientific research and conservation for the development of botanical, horticultural, agricultural and other related fields. There are various types of interpretation products in TBNSA consisting of signages, panel boards, exhibits, replicas, maps, and more. To ensure that all information and messages conveyed through interpretation products are effective and understandable to visitors, the contents of the information and messages in the product need to be explained on the basis of six key principles of interpretation by Freeman Tilden. Not only that, the design of interpretation products such as signboards, should also be based on interpretation standards such as the correct use of writing types and signs. Hence, this study aims to identify the effectiveness of message content on interpretive signages in TBNSA based on principles of interpretation and objectives of interpretation. It also aims to evaluate the design features of interpretation products, especially signages in TBNSA based on interpretation standards. The results show that most interpretation products, especially signages in TBNSA, adhere to principles of interpretation, especially 'relate' and 'provoke' principles, but there are many interpretation products such as signages and panel boards that do not have message theme. This can make readers confused about the actual objective to be delivered through such messages or information. Additionally, most of the designs of interpretive signages at TBNSA achieve interpretation standards such as the use of the correct size of the writing and colour of the signages that related with the site. In conclusion, improvements to interpretation products in TBNSA, especially signages, need to be done to ensure the effectiveness of message contents and information to visitors and interpretation objectives can be achieved.